PENGARUH GOAL-SETTING TERHADAP PENINGKATAN MOTIVASI PADA TIM BASKET PUTRA SMA NEGERI 1 TEBING TINGGI - Atika, Nur; Wijayanti, Ni Putu Nita; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The problem in this research is that these athletes have low motivation, show little interest, lack attention during training, do not focus physically and psychologically, often feel bored and give up, often give up, lack encouragement and unclear direction which makes them less enthusiastic while practicing. The aim of this researcher is to determine the effect of goal-setting on increasing motivation in the men's basketball team at SMA Negeri 1 Tebing Tinggi. This research method is a pre-experimental design research, the research design used is pretest-posttest one group design. The population in this study was 11 students of SMA Negeri 1 Tebing Tinggi. The instrument used in this research was a questionnaire. Data analysis techniques use normality tests and t tests, to determine the effect before and after the treatment or treatment given. Based on the results of the hypothesis test analysis, the value obtained is tcount (19.818) > ttable (1.796) at a significance level of α = 0.05 for a sample size of 11. So it can be concluded that Ho is rejected and Ha is accepted. Thus, it can be concluded that there is an influence of goal-setting on increasing motivation in the men's basketball team at SMA Negeri 1 Tebing Tinggi.Key Words: Effect of goal-setting, motivation, basketball.